OWE-27 Analysis of UC colectomy rates in pre- and post- biologic era South-East Scotland. Issue 2 (June 2019) - Jenkinson, Philip; Jones, Gareth; Plevris, Nik; Lyons, Mathew; Kirkwood, Kate; Wilson, David; Dunlop, Malcolm; Arnott, Ian; Lees, Charlie
Abstract : Introduction: The use of biologic therapy for UC has lagged significantly behind that of Crohn's Disease in part because of restricted guidance from NICE. Following approvals of anti-TNF and vedolizumab for UC in early 2015 a significant increase in prescribing has been reported. Whether this has resulted in a decrease in colectomy rates has not been studied in a real-world setting. The aim of this study was to describe trends in colectomy rates for UC over time spanning the pre- and post-biologic era. Methods: All patients (adult and paediatric) with a diagnosis of UC who received maintenance biologic treatment and/or underwent a colectomy in Lothian, Scotland between 1st January 2005 and 31st December 2018 were identified by interrogating multiple clinical and administrative databases. Patient phenotype, prescribing and surgical data including complications were extracted by manual review of the electronic medical record. Linear and segmental regression were used to identify changes in the trend of biologic prescription and colectomy rates and to estimate the annual percent change. Colectomy rates were described per 100 UC patients, with yearly prevalence data obtained from the Lothian IBD Registry. Results: Of 175 patients treated with maintenance biologic therapy 14 (8%) were initiated 2005 to 2013 and 161 (92%) from 2014 to 2018 (Figure 1A). The number of patients starting treatment per year increased from 0.06 in 2005 to 1.37 in 2018 per 100 UC patients (p<0.001). A total of 448 patients underwent colectomy. Colectomy rates per 100 UC patients fell throughout the study period; from 1.84 in 2005 to 0.45 in 2018 (p<0.001). On segmental regression a joinpoint was identified at 2014; the annual colectomy rate fell by 5.81% per year from 2005 to 2014 and by 17.41% per year from 2014 to 2018 (p<0.05). 41/175 patients underwent colectomy following biologic treatment (median duration 7.5 months), there was no increase in post-operative complication rates in biologic exposed patients vs no biologics. Conclusion: The increase in biologic prescribing for UC has been parallelled by a significant reduction in colectomy rates without increased post-operative complications. Whilst we cannot ascribe causality further work is under way to expand this cohort across Scotland.